Upaya Peningkatan Pertumbuhan dan Produksi Gambas Melalui Pengaturan Jarak Tanam dan Waktu Penyiangan di Lahan Kering - Gribaldi Gribaldi; Nurlaili Nurlaili (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2018)
Gribaldi et al, 2018. Increasing the Growth and Production of Oyong Through Setting the Planting Distance and Weeding Period in Dry Land. JLSO 7(2):157-163.Â Luffa acutangula (angled loofah) provide great benefits so that it is popular and consumed by the public. The increasing of L. acutangula production continues to be carried out in line with increasing market demand, one of them is through the improvement of cultivation techniques, such as fertilizer application, spacing and time for weeding. This study aimed to determine the increase in growth and production of L. acutangula plants at various planting distances and weeding time. This study used a randomized block design which was arranged through factorial with three replications. The factors studied consisted of: plant spacing (J), spacing of 40 cm x 50 cm (J1), spacing of 60 cm x 50 cm (J2), and spacing of 80 cm x 50 cm (J3). Weed weeding treatment (P) consists of: No weeding (P0), weeding at 15 DAS (days after sowing) (P1), weeding at 25 DAS (P2), weeding at 35 DAS (P3), and weed-free (P4). The results showed that the treatment of plant spacing and weeding time affected the plant growth and production. Spacing at 40 cm x 50 cm resulted in the best of plant growth and yield, and weeding at 35 DAS and weed-free plant produced the best growth and yield.